Propiedades Mecánicas de los Alambres de Ortodoncia Gummetal® y Níquel -Titanio, Mediante Ensayos Mecánicos. (2021)
The purpose of this study was to compare the mechanical properties (máximum strength, strength at elastic limit, stiffness and range) of rectangular Gummetal® and Nickel-Titanium Superelastic wires, through Load-Deflection and Tension-Stress tests.